POLITIK TUBUH DALAM SERAT KAWRUH SANGGAMA KARYA RADEN BRATAKESAWA AWAL ABAD XX - Adi Putra Surya Wardhana; Fiqih Aisyatul Farokhah (Patanjala: Journal of Historical and Cultural Research, 2021)
Hal-hal yang berkaitan dengan seksualitas selalu menarik untuk dikaji meskipun diikat oleh tabu. Pada awal abad XX, naskah-naskah soal seksualitas cukup populer, apalagi sudah dicetak dalam bentuk buku yang diperjualbelikan di lapak-lapak buku. Salah satu naskah yang memuat seksualitas adalah Serat Kawruh Sanggama. Tujuan penelitian ini adalah untuk mengungkap bentuk, fungsi, dan makna politik tubuh dalam Serat Kawruh Sanggama. Metode yang digunakan adalah analisis data kualitatif-interpretatif dengan pendekatan teori politik tubuh. Hasil penelitian menunjukkan, Serat Kawruh Sanggama ditulis di Kediri dan disebarluaskan oleh penerbit Boekhandel Tan Khoen Swie Kediri. Bentuk politik tubuh berupa narasi tentang tata cara atau aturan bersenggama. Naskah ini mengandung politik tubuh yang berfungsi untuk menundukkan, mengontrol, dan mendominasi tubuh perempuan. Namun demikian, naskah ini dapat dimaknai sebagai upaya laki-laki untuk memahami misteri tubuh perempuan. Selain itu, naskah ini dimaknai pula sebagai daya perempuan, sehingga laki-laki harus berusaha untuk memahami seluk beluk tubuh perempuan.Despite a taboo subject amongst society, the matters related to sexuality are always interesting to study. In the early twentieth century, texts on sexuality were quite popular and had even been printed in the form of books that were sold in the book stalls. One of those was Serat Kawruh Sanggama. The purpose of this study was to analyze the form, the function, and the meaning of the politics of the body in the Serat Kawruh Sanggama. The method used in the research was the qualitative-interpretative data analysis combined with the approach of the Politics of the Body. The results of the study have shown that Serat Kawruh Sanggama was written in Kediri and then disseminated by the publisher of the Boekhandel Tan Khoen Swie Kediri. The elements of the Politics of the Body revealed in the text are in the form of narratives related to the procedures or rules of sexual intercourse. It is evident that the elements of the Politics of the Body found on the text served as an instrument of subjugating, controlling, and dominating the female body. This text can be interpreted as an attempt by men to understand the mystery of the female body. However, on the other hand, the text can also be interpreted as an attempt by men to understand the mystery of the female body. In addition, it also represented as a woman's power that encourages men to understand the ins and outs of the female body.